Nodo-Colonic Fistula Caused by Intra-Abdominal Tuberculous Lymphadenitis during Treatment with Anti-Tuberculous Medication: A Case Report - Nam, Kyungsun; Bae, Kyung Eun; Jeong, Myeong Ja; Lee, Ji Hae; Kang, Mi-Jin; Kim, Jae Hyung; Kim, Soo Hyun (Journal of the Korean Society of Radiology, 2016)
Recently, the overall incidence of tuberculosis has decreased, but the incidence of an extrapulmonary manifestation in patients with tuberculosis has increased in the Republic of Korea. Although intestinal tuberculosis is not infrequent, a fistula caused by tuberculosis is a rare condition. A 23-year-old man presented with fever, diarrhea and right lower quadrant pain. A computed tomography (CT) scan revealed a lobulated, peripherally enhancing, low density mass in the mesentery. The patient underwent laparoscopic biopsy for necrotic lymph node, and intra-abdominal tuberculous lymphadenitis was diagnosed. Four months after initiating treatment with anti-tuberculous medication, the patient developed fever together with lower abdominal pain. A follow-up CT scan revealed a fistulous tract that had developed between the initially noted lymphadenopathy and the proximal ascending colon. Laparoscopic right hemicolectomy was performed as a curative treatment. This case suggests that a nodo-colonic fistula may occur as a paradoxical response in patients with intra-abdominal tuberculous lymphadenitis during treatment with anti-tuberculous medication.